Observation of Ice-Like Two-Dimensional Flakes on Self-Assembled Protein Monolayer without Nanoconfinement under Ambient Conditions - Peng, Wuxian; Li, Linbo; Bai, Xiyue; Yi, Ping; Xie, Yu; Wang, Lejia; Du, Wei; Wang, Tao; Zhong, Jian‑Qiang; Li, Yuan (Nano-Micro Letters, 2025)
Directly correlating the morphology and composition of interfacial water is vital not only for studying water icing under critical conditions but also for understanding the role of protein–water interactions in bio-relevant systems. In this study, we present a model system to study two-dimensional (2D) water layers under ambient conditions by using self-assembled monolayers (SAMs) supporting the physisorption of the Cytochrome C (Cyt C) protein layer. We observed that the 2D island-like water layers were uniformly distributed on the SAMs as characterized by atomic force microscopy, and their composition was confirmed by nano-atomic force microscopy-infrared spectroscopy and Raman spectroscopy. In addition, these 2D flakes could grow under high-humidity conditions or melt upon the introduction of a heat source. The formation of these flakes is attributed to the activation energy for water desorption from the Cyt C being nearly twofold high than that from the SAMs. Our results provide a new and effective method for further understanding the water–protein interactions. Highlights: 1 A super-hydrophilic electrode was successfully developed by depositing porous NiFe nanoparticles onto annealed TiO2 nanotubes (NiFe/ATNT), facilitating rapid outgassing of nonpolar gases. 2 The NiFe/ATNT electrode demonstrated an overpotential of 235 mV at 10 mA cm−2 for the oxygen evolution reaction in 1.0 M KOH and served as the anode in the anion exchange membrane water electrolyzer (AEMWE), achieving a current density of 1.67 A cm−2 at 1.80 V. 3 The AEMWE utilizing the NiFe/ATNT electrode exhibited remarkable stability, maintaining operation for 1500 h at 0.50 A cm−2 under challenging thermal conditions of 80 ± 3 °C.